Novel Simian Homologues of Epstein-Barr Virus - Ehlers, Bernhard (American Society for Microbiology, 2003)
Thirty different lymphocryptoviruses (LCV), 26 of them novel, were detected in primates by a panherpesvirus PCR assay. Nineteen LCV from chimpanzees, bonobos, gorillas, and other Old World primates were closely related to Epstein-Barr virus (EBV), the type species of the genus Lymphocryptovirus. Seven LCV originating from New World primates were related to callitrichine herpesvirus 3 (CalHV-3), the first recognized New World LCV. Importantly, a second LCV from gorillas and three LCV from orangutans and gibbons were only distantly related to EBV and CalHV-3. They were tentatively assigned to a novel genogroup of Old World primate LCV. The work described in the paper may also help identify an as yet unknown human LCV.